Between Scylla and Charybdis: Fixed-Ratio Avoidance Response Effort and Unavoidable Shock Extinction in Humans - Simon Dymond (Behavioural Brain Research, 2025)
Avoidance of potential threat may become maladaptive when it is indiscriminate and resistant to change. Here, we investigated the resistance to change of high and low avoidance response effort when avoidance extinction involved unavoidable presentations of the aversive event (shock) in humans. Following fear conditioning, participants prevented upcoming shock delivery by responding on high (i.e., fixed ratio, FR-20) and low (FR-5) negative reinforcement schedules. Next, noneliminable shock was used for an avoidance extinction procedure whereby responding was followed by, rather than prevented, shock. During a subsequent standard extinction and response prevention test phase, we found that High effort (FR-20) avoidance would be more readily extinguished than Low effort (FR-5) avoidance. It was also predicted that fear, threat expectancy, and psychophysiological (skin conductance) responses would decrease on avoidable trials and increase on unavoidable trials before extinguishing to low levels. It was found that in the final extinction re-test phase when avoidance was possible, responding increased, particularly for low effort cues. Both fear and expectancy remained high. Individual differences on clinically relevant measures of trait anxiety, intolerance of uncertainty and experiential avoidance were associated with greater levels of fear and threat expectancy. Overall, unavoidable shock extinction may hold promise for further translational investigations of avoidance learning, extinction, and clinical treatment development.